Sexual Dimorphism of Dried Hip Bones with Respect to Chilotic Index: A Study on the Population of Andhra Pradesh, India - Baa, Jeneeta; Maharana, P.C. (Medicine and Medical Research: New Perspectives Vol. 3, 2024)
Sexual dimorphism refers to the difference between males and females in regard to their size and appearance. Different populations differ with regard to the body built of a person and the degree of sexual dimorphism. The aim of this study is to determine the sexual dimorphism of dried human hip bone with respect to chilotic line and chilotic index (CI) and find a cut-off value for the chilotic index that will be accurate for identification of sex in the human hip bone. The study was undertaken with a sample size of 44 adult human dried hip bones from the Department of Anatomy GVP.I.H.C & MT, Visakhapatnam, Andhra Pradesh, India. The Chilotic line (sacral segment and pelvic segment) was measured using a Vernier calliper and the chilotic index was calculated. The statistical analysis of the data was done by using SPSS version 22. The chilotic index in male hip bones falls in the range of 102.77mm-139.46mm with a mean value of 118.32mm and for females, it lies in the range of 61.63mm–98.17mm with a mean value of 84.84mm. This finding is statistically significant with a p-value = <0.001. The total chilotic line in males is longer than in females and a cut-off value of 100.48 is statistically 100% correct in identification of a male and a female hip bone. The sex of the Hip bone can be assessed up to about 97% confidence with the help of “Chilotic line” and “Index” only.